2012
DOI: 10.1039/c2cc33797e
|View full text |Cite
|
Sign up to set email alerts
|

Template-free synthesis of mesoporous N-doped SrTiO3 perovskite with high visible-light-driven photocatalytic activity

Abstract: An effective, template-free synthesis methodology has been developed for preparing mesoporous nitrogen-doped SrTiO 3 (meso-STON) using glycine as both a nitrogen source and a mesopore creator. The N-doping, large surface area and developed porosity endow meso-STON with excellent activity in visible-light-responsive photodegradation of organic dyes.The exceptional electro-optical properties and physicochemical stability of the perovskite SrTiO 3 (STO) give rise to its attractive performance in photocatalytic ap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
91
0
4

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 138 publications
(103 citation statements)
references
References 32 publications
3
91
0
4
Order By: Relevance
“…However, broad N 1s peaks appear within 397-402.5 eV for the meso-TON materials, which can be attributed to different nitrogen species, such as substitutional NO x (Ti-(NO) x , 398.7-399.5 eV) and interstitial NO x (398.2-398.5 eV and 400-402 eV). 16,32 Such broad N 1s XPS spectra due to various NO x -dopants have ever been observed in the N-doped TiO 2 .…”
Section: 1227mentioning
confidence: 99%
See 3 more Smart Citations
“…However, broad N 1s peaks appear within 397-402.5 eV for the meso-TON materials, which can be attributed to different nitrogen species, such as substitutional NO x (Ti-(NO) x , 398.7-399.5 eV) and interstitial NO x (398.2-398.5 eV and 400-402 eV). 16,32 Such broad N 1s XPS spectra due to various NO x -dopants have ever been observed in the N-doped TiO 2 .…”
Section: 1227mentioning
confidence: 99%
“…5B, while broadening of O 1s at 531 eV can be clearly observed which was previously attributed to the presence of the N-Ti-O and O-N-Ti-O bond. 13,16,33 The broadening of O 1s spectra in 531-532.5 eV may be assigned to the surface hydroxyl groups on titania. The three samples are of very similar C 1s XPS spectra centred at 285 eV (Fig.…”
Section: 33mentioning
confidence: 99%
See 2 more Smart Citations
“…Three new bands around 1630, 1490, and 1330 cm -1 were observed for nitrogen doped compounds which are characteristic of N-doped oxides. [9,10] It was reported that, N-doped SrTiO 3 show surface N-H band at 1633 cm -1 , nitrite peak at 1453 cm -1 and hyponitrite peak at 1396 cm -1 . So, in NaSPON, AgSPON, and CuSPON, the bands observed around 1630, 1490, and 1330 cm -1 correspond to surface N-H, nitrite, and hyponitrite species, respectively.…”
Section: Scanning Electron Microscopy -Energy Dispersive Spectroscopymentioning
confidence: 98%